The Impact of Debt Sustainability and the Level of Debt on Emerging Markets Spreads - Belhocine, Nazim; Dell'Erba, Salvatore (Washington, D.C. : International Monetary Fund, 2013)
How do financial markets respond to concerns over debt sustainability and the level of public debt in emerging markets? We introduce a measure of debt sustainability - the difference between the debt stabilizing primary balance and the primary balance-in an otherwise standard spread regression model applied to a panel of 26 emerging market economies. We find that debt sustainability is an important determinant of spreads. In addition, using a panel smooth transition regression model, we find that the sensitivity of spreads to debt sustainability doubles as public debt increases above 45 percent of GDP. These results suggest that market interest rates react more to debt sustainability concerns in a country with a high level of debt compared to a country with a low level of debt.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet